Antecedent of Event Satisfaction Towards Revisit Intention Tambora Event Indonesia - Jumraidin Jumraidin; Li Wei Liu (Politeknik Pariwisata Lombok, 2022)
This study aimed to review the influence of event destination attributes and service quality on event satisfaction of revisit intention. This study using sampling methods by online questionnaire to the visitors. A total of 234 respondents were collected. The descriptive statistical and structural equation model, or SEM-PLS, were utilized for analysis in this study. The findings of the PLS-SEM study in the overall model, event destination attributes did not directly influence event satisfaction; however, it showed an indirect effect.